Surgical treatment of posterior interosseous nerve paralysis in a tennis player() - Fujioka, Hiroyuki (Elsevier, 2014)
We report a rare case of posterior interosseous nerve (PIN) paralysis in a tennis player. The PIN, a 2 cm section from a bifurcation point of the radial nerve, presented increased stiffness in the surgical findings and treated with free sural nerve grafting after excision of the degenerative portion of the PIN. We speculate that PIN paralysis associated with hourglass-like constriction can be caused and exacerbated by repetitive forearm pronation and supination in playing tennis.